Experimental device to measure the compressibility coefficient of soft materials - N. Briot; G. Chagnon; N. Connesson; T. Alonso; P.-A. Barraud; Y. Payan (PLoS ONE, 2025)
At present, there are many ways to measure the compressibility coefficient of a sample, but none of them allow the measurement of compressibility on samples that cannot be cut to a precise shape, such as human soft tissue, rubber-like materials and polymers. The objective of this study is therefore to demonstrate the proof of concept of a device allowing the measurement of the compressibility coefficient on a sample which is non-cuttable in a precise shape. The device is made of a cylindrical chamber, filled with a liquid, in which a sample of the soft material is inserted. The volume of the chamber is decreased by means of the insertion of a piston while the resulting pressure variation is measured. The compressibility coefficient of the soft material is then estimated from the pressure-volume curves. The results obtained on two industrial materials, namely a PMMA and a SBR rubber, show that the method produces similar results than those obtain by a classical stereocorrelation analysis on a tensile test. These results give confidence in the coefficients obtained with the compressibility method and open perspectives for human soft tissues.